2015
DOI: 10.4028/www.scientific.net/amr.1114.92
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Conductive Polymer Nanocomposites Based on Ethylene–Vinylacetate Copolymer (EVA) Reinforced with Expanded and Unexpanded Graphite

Abstract: Recently polymer nanocomposites are used more and more frequently in industry due to the fact that the properties of the polymers can be altered to the specific requirements by the addition of particles and fibers of different properties, shapes. Polymers are poor thermal and electrical conductors, conductive fillers such as metallic powders, carbon black, graphite, are usually incorporated into polymer matrix to produce conducting composites. In this study composites were prepared using ethylenevinyl acetate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Specifically, we seek to understand how a 1−3 nm coating would enable electronic conductivity or facilitate fast ion transport through an amorphous carbon layer, resulting in the reported improved electrochemical performances. We note that amorphous or disordered carbons tend to have electronic conductivities 1000× lower than graphene or graphite, 23 making simple electronic pathway arguments more challenging to accept. We demonstrate through Raman mapping, electron microscopy, XPS, EIS, and zeta potential measurements that the structure of the electrodes improves with carbon coating due to a matching of the materials' surface chemistry.…”
Section: ■ Introductionmentioning
confidence: 91%
“…Specifically, we seek to understand how a 1−3 nm coating would enable electronic conductivity or facilitate fast ion transport through an amorphous carbon layer, resulting in the reported improved electrochemical performances. We note that amorphous or disordered carbons tend to have electronic conductivities 1000× lower than graphene or graphite, 23 making simple electronic pathway arguments more challenging to accept. We demonstrate through Raman mapping, electron microscopy, XPS, EIS, and zeta potential measurements that the structure of the electrodes improves with carbon coating due to a matching of the materials' surface chemistry.…”
Section: ■ Introductionmentioning
confidence: 91%
“…A similar assumption was used earlier for predicting tensile modulus of various hybrid systems. [4,54] For all the calculations, thermal conductivity of PP, CF, and HGM were taken as 0.22 W/m K, [55] 22 W/m K, [56] and 0.153 W/m K [48] , respectively. For simplicity, the effect of MA-g-PP was not considered during the analysis.…”
Section: Thermal Analysismentioning
confidence: 99%
“…2(c). These results indicated that the PEDOT:PSS changed to have the property of a conductive electrode (Au: 4.1 × 10 7 S m −1 , Pt: 9.4 × 10 6 S m −1 , glassy carbon: 2.2 × 10 4 S m −1 , graphite: 2.1 × 10 3 S m −1 ) [45][46][47] at strongly acidic condition. 37,38 Additionally, the peak potential separation (ΔE p = E ap − E cp ) between the cathodic and anodic peaks of CV was observed to be decreased at strongly acidic condition from the comparison of the cyclic voltammograms of TMB.…”
Section: Properties Of Vpe Based On Pedot:pssmentioning
confidence: 89%